Legal terminology explained - Nolfi, Edward A. (McGraw Hill, 2009)
Legal Terminology Explained for Paralegals is designed for students and teachers in legal career programs, in law-related programs, and in programs that overlap the law. It provides accurate definitions to law-related words and phrases and discusses each word and phrase in a brief narrative among related words and phrases, in a logical progression, according to a high-level outline. It strips legal terminology of its oftentimes confusing, excessive, or unnecessary explanations and in turn, provides the student with clear and concise definitions.